2011
DOI: 10.3233/wor-2011-1270
|View full text |Cite
|
Sign up to set email alerts
|

Work week duration, work-family balance and difficulties encountered by female and male physicians: Results from the French SESMAT study

Abstract: Objective: France encounters difficulties attracting physicians to work in hospitals. Organisation at work and at home may be at the heart of the problem for female as well as for male physicians. Participants: A comprehensive questionnaire was filled out online by a representative sample of 1924 French hospital physicians. Methods: We conducted gender bivariate and multivariate analysis of the risk factors for burnout and intent to leave the profession(ITL). Results: ITL was declared by 17.4% of physicians. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 41 publications
2
30
0
6
Order By: Relevance
“…The first theme, derived from one qualitative study (20 participants) 10 and ten quantitative cross-sectional surveys (183 to 6880 participants), 8,[11][12][13][14][15][16][17][18][19] was the influence of a medical career on decisions and priorities related to motherhood, including decisions about whether to have children, and when and how many, as well as the ongoing effect of a medical career on a woman's family (Supporting Information, table 2).…”
Section: Motherhood: the Impact Of Being A Doctor On Raising Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…The first theme, derived from one qualitative study (20 participants) 10 and ten quantitative cross-sectional surveys (183 to 6880 participants), 8,[11][12][13][14][15][16][17][18][19] was the influence of a medical career on decisions and priorities related to motherhood, including decisions about whether to have children, and when and how many, as well as the ongoing effect of a medical career on a woman's family (Supporting Information, table 2).…”
Section: Motherhood: the Impact Of Being A Doctor On Raising Childrenmentioning
confidence: 99%
“…Five studies reported that women who were doctors described decisions about having children or pursuing career progression as difficult. 10,12,13,16,18 Most participating women reported prioritising their careers, including completion of specialty training, by choosing to delay having children. 10,13,16,18 In one study, 12 513 of 801 respondents (64%) deferred having children for career reasons.…”
Section: Motherhood: the Impact Of Being A Doctor On Raising Childrenmentioning
confidence: 99%
“…D'un côté, la population et les politiciens demandent aux médecins d'en faire plus, et de l'autre, les médecins trouvent qu'ils en font trop et se sentent épuisés. « La perception qu'a la société des médecins, soit le fait qu'ils sont des privilégiés, hautement éduqués, bien rémunérés pour un travail qui est reconnu et valorisé n'est pas conforme à la réalité » [15], et leurs difficultés sont bien documentées dans la littérature [16][17][18]. La perception sociale que les médecins ne prennent pas leurs responsabilités serait en fait fausse, c'est plutôt qu'ils sont incapables de répondre à la demande en raison d'un épuisement.…”
Section: êTre Médecin : Une Responsabilité Socialeunclassified
“…En los últimos 30 años, la proporción de mujeres que estudian medicina ha crecido de forma constante en numerosos países, incluido Estados Unidos [1], Canadá [2,3], Reino Unido [4], Francia [5], Japón [6], Israel [7] y Australia [8]. En Argentina también se evidencia un proceso de feminización de la profesión médica que comienza en la universidad y se extiende al ámbito del ejercicio profesional [9].…”
Section: Introductionunclassified